Gambaran Tingkat Pengetahuan Masyarakat Dalam Pengobatan Gastritis Di Dusun Pringgolayan Banguntapan Bantul: Description Of The Level Of Public Knowledge In The Treatment Of Gastritis In Pringgolayan Banguntapan Bantul - Chantika, Yustina Esha Maunia; Yulianto , Danang (Jurnal Inovasi Farmasi Indonesia (JAFI), 2025)
According to the World Health Organization (WHO) in 2020, the largest gastritis sufferers occurred in Canada as much as 35%, China 31%, France 29.5%, Japan 14.5% while Indonesia reached 40.8%. Patients with gastritis in Indonesia reached 274,396 patients out of 238,452,952 population. The increase in incidence is influenced by a lifestyle that pays less attention to health. The majority of public knowledge about gastritis treatment is still in the poor category. This study aims to determine the description of the level of public knowledge in the treatment of gastritis in Pringgolayan Hamlet Banguntapan Bantul. The research method used descriptive observational with sampling using purposive sampling with a population of 2,931 people and a sample of 100 respondents. The data observed included the level of knowledge in the treatment of gastritis in Pringgolayan Hamlet. The data were then analyzed descriptively with the level of knowledge of good, sufficient, and less. The results of the study on the description of the level of knowledge of the community in the treatment of gastritis showed that the level of knowledge of respondents in the good category 51 respondents (51%), sufficient knowledge 44 respondents (44%), and less knowledge 5 respondents (5%). Based on the research that has been carried out, it can be concluded that the majority of people's knowledge level in the treatment of gastritis is good.